BeeCrobes, UMPSA researchers’ innovation, discovers potential of stingless bee honey as natural probiotic source - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 15 October 2025 – Researchers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) successfully developed the first probiotic supplement product based on local stingless bee honey, named BeeCrobes.